2007
DOI: 10.3844/ajabssp.2007.81.87
|View full text |Cite
|
Sign up to set email alerts
|

Maize Oil Can Replace Fish Oil in The Diet of Grouper Postlarvae (Epinephelus Coioides) Without Adversely Affecting Growth or Fatty Acid Composition

Abstract: This experiment was conducted to evaluate the effects of dietary lipid sources on growth, survival and body composition of 40 day post hatch larval grouper, Epinephelus coioides. Fish were fed fish meal and protein hydrolysate based diets for 32 days with either 100% maize oil or 100% fish oil in triplicate from 40-day after hatching to slaughter size (fish weight: 0.32 g to 11 g). Final body wet weight (FBW: 11.8±0.7 and 11.1±0.1, respectively), weight gain (WG: 3556±251 and 3360±189, respectively), specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Hypercholesterol and fatty acids in plasma are the main causes for cardiovascular disease (Talon et al, 2000;Niu et al, 2007). Sindhu and Khetarpaul (2003) reported that 1% reduction in plasma cholesterol was associated with reductions of 2-3% in the risk of coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…Hypercholesterol and fatty acids in plasma are the main causes for cardiovascular disease (Talon et al, 2000;Niu et al, 2007). Sindhu and Khetarpaul (2003) reported that 1% reduction in plasma cholesterol was associated with reductions of 2-3% in the risk of coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…The use of maize oil in diet of grouper resulted in substantial growth and excellent feed efficiency. Grouper seem able to efficiently utilize maize oil as the dietary lipid source as long as their requirement for essential fatty acids are met (Niu et al, 2007). A larger number of plants and their isolated constituents have been shown to modulate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the growth rate (WGR, SGR), feed utilization (FCR, PER), and body lipid content of the hybrid grouper were depressed by dietary supplementation with 8.86 and 17.72 mg/kg MDA in this study. Additionally, previous studies showed that oxidized oil inhabited the growth rate of orange spotted grouper Epinephelu coioides [23,24], Japanese sea bass Lateolabrax japonicus [25], Rhynchocypris lagowski Dybowski [26], Wuchang bream Megalobrama amblycephala [27], tilapia Oreochromis niloticus [28] and pearl gentian grouper Epinephelus fuscoguttatus♀× E. lanceolatus♂ [19]. It deemed that the adverse effect of oxidized oil on the lipid digestion and absorption of grass carp [6] may mainly be attributed to dietary MDA present in oxidized oil.…”
Section: Discussionmentioning
confidence: 99%